Environment and development : gender perspective - Jahan, Roushan; Women for Women (Organization : Bangladesh); National Convention 1993 on Environment and Development: Gender Perspective (1993 : Dhaka, Bangladesh) (Dhaka : Women for Women, 1995)
Papers presented at the National Convention 1993 on Environment and Development: Gender Perspective, held in Dhaka, 27-28 Nov. 1993.
Includes bibliographical references.
Keywords: Women in development -- Bangladesh -- Congresses; Women and the environment -- Bangladesh -- Congresses; Environmental policy -- Bangladesh -- Congresses; Economic development -- Environmental aspects -- Bangladesh -- Congresses